2014
DOI: 10.1098/rsif.2014.0264
|View full text |Cite
|
Sign up to set email alerts
|

Robustness of differentiation cascades with symmetric stem cell division

Abstract: Stem cells (SCs) perform the task of maintaining tissue homeostasis by both self-renewal and differentiation. While it has been argued that SCs divide asymmetrically, there is also evidence that SCs undergo symmetric division. Symmetric SC division has been speculated to be key for expanding cell numbers in development and regeneration after injury. However, it might lead to uncontrolled growth and malignancies such as cancer. In order to explore the role of symmetric SC division, we propose a mathematical mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…In previous, non-spatial models, it was shown that symmetric stem cell divisions help delay the production of double-hit mutant compared to asymmetric stem cell divisions [ 19 , 20 , 22 ]. In the present model, the same trend is observed (see e.g.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous, non-spatial models, it was shown that symmetric stem cell divisions help delay the production of double-hit mutant compared to asymmetric stem cell divisions [ 19 , 20 , 22 ]. In the present model, the same trend is observed (see e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, for intestinal crypts there are reports that an age-dependent transition occurs from mainly asymmetric divisions to largely symmetric divisions [ 15 ], and opposing reports that a transition occurs from symmetric to asymmetric divisions [ 16 ]. The potential tradeoffs between symmetric and asymmetric stem cell divisions in tissues have previously been considered by many modelers using ODE models [ 17 ], stochastic space-free models [ 18 22 ], and in a spatial setting [ 23 ]. Several of these models consider the time to appearance of k consecutive mutations in a population of cells, and ask how mutation accumulation can be minimized.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an asymmetric division, stem cells divide to generate one daughter cell with self renewal capacity and other which differentiates. In a symmetric division, there are two types-proliferation division, in which stem cell divide to generate two stem cells and differentiation division where parent cell gives rise to two differentiated cells [33][34][35]. Molecular mechanisms which underlie the regulation of self-renewal are yet ripe for research.…”
Section: Wnt Signaling In Hematopoiesis Hematopoiesismentioning
confidence: 99%
“…Dynamic model of cell population can be represented by the following system of ordinary differential equations [2]:…”
Section: Model Descriptionmentioning
confidence: 99%